1997
DOI: 10.1029/97jb01275
|View full text |Cite
|
Sign up to set email alerts
|

On the variability of the Chandler frequency

Abstract: Abstract. We have estimated the Chandler frequency from a variety of polar motion time series derived from optical and space geodetic data which span various time periods from 1846 through the early 1990s. Estimates of F vary, depending upon which time series is employed, but the variation is not significant when associated intervals of confidence are considered; thus there is no evidence that the true Chandler frequency has varied. Using a maximum likelihood method, our preferred estimate of F is 0.8433 cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 20 publications
5
22
0
Order By: Relevance
“…The theoretical computation of σ c leads to a period of 430.3 days and a quality factor Q = 88 (Mathews et al 2002). The theoretical period is consistent with other estimates of the observed Chandler period based on analyses of polar motion time series (e.g., Vicente & Wilson 1997). However, there is no consensus on the value of Q: depending on the time interval and the analysis method, it ranges from 50 (Furuya & Chao 1996;Kuehne et al 1996) to 180 (Vicente & Wilson 1997;Aoyama et al 2003).…”
Section: The Polar Motion Excitation By Fluid Layerssupporting
confidence: 73%
See 2 more Smart Citations
“…The theoretical computation of σ c leads to a period of 430.3 days and a quality factor Q = 88 (Mathews et al 2002). The theoretical period is consistent with other estimates of the observed Chandler period based on analyses of polar motion time series (e.g., Vicente & Wilson 1997). However, there is no consensus on the value of Q: depending on the time interval and the analysis method, it ranges from 50 (Furuya & Chao 1996;Kuehne et al 1996) to 180 (Vicente & Wilson 1997;Aoyama et al 2003).…”
Section: The Polar Motion Excitation By Fluid Layerssupporting
confidence: 73%
“…In the absence of forcing, the CW would have a period of 430.3 days (Mathews et al 2002) fixed mainly by the whole planet's dynamical ellipticity and, more marginally, by mantle and ocean deformabilities, and would lose most of its energy after a few tens of years because of dissipation in the mantle and in the oceans. Observation of the Earth's polar motion, however, reveals a prograde oscillation whose pseudo period can be as far as 20 days from the above value (e.g., Vondrák 1988;Vicente & Wilson 1997). It gains energy at some times (e.g., Danjon & Guinot 1954) so that it never disappears.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This rst order equation is based on the linearisation of the original EulerLiouville equation and is a simple but an adequate approximation of the real system, Munk and MacDonald (1960), Wilson and Chen (1996), Vicente and Wilson (2002), Bizouard and Seoane (2010). In the works of Vicente and Wilson (1997), Spiridonov and Tsurkis (2008), Furuya and Chao (1996) (1) has the form Developed in the works of Wilson (1985), Wilson and Chen (1996), Vicente and Wilson (2002) and improved in Zhou et al (2005) Jereys-Wilson lter is a convenient way to reconstruct the excitation from discrete equally spaced observations…”
Section: Dynamical Modelling and Excitation Reconstructionmentioning
confidence: 99%
“…Some researchers have suggested that the CW is highly variable with respect to its amplitude (e.g., Carter, 1981Carter, , 1982Höpfner, 2003;Chen et al, 2009Chen et al, , 2013a, some have considered it to have double or multiple frequencies (e.g., Chao, 1983;Pan, 2012), and some have considered its frequency to be invariant (e.g., Okubo, 1982;Vicente and Wilson, 1997;Gross et al, 2003;Seitz and Schmidt, 2005). If the CW is frequency modulated as Carter (1981Carter ( , 1982 suggested, namely, the frequency is governed by the magnitude, it will create an infinite number of sidebands, arranged symmetrically about the carrier and spaced at integer multiples of the modulating frequency (Carter, 1981).…”
Section: Introductionmentioning
confidence: 99%